Cochlear Implantation: Predicting Round Window Niche Visibility Using One Measurement in High-Resolution Temporal Bone Computed Tomography - Laila Telmesani; Mona Al-Ramah; Yassin Abdelsamad; Lena Telmesani (Journal of International Advanced Otology)
BACKGROUND: To evaluate the accuracy of a single measurement in temporal bone computed tomography in predicting the round window niche (RWN) visibility during cochlear implantation.